PERDAGANGAN SAHAM DALAM ISLAM - Suprihatin . (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2002)
Trade of exchange is something contemporary that had never been identified in the age of Rasulullah, of sahabat, or of Tabi’in. where is the position of trade of exchange in Islamic Law? This is issue will be discussed in this moment